Requiem, d’Antonio Tabucchi ou l’aventure portugaise d’un Italien - Aina López Montagut (Catalonia)
Alloglossia can be explained in different ways: whether for political, socio-cultural, emotional or other reasons, the authors concerned justify their linguistic choices to some extent. Whether they simply write in the other language, or decide to create a literary bridge between two language systems, the writing they produce reflects a willingness and sometimes even evidence of linguistic acquisition, as well as a high degree of inter-comprehension between the languages used.We will focus here on the case of the Italian author Antonio Tabucchi, and particularly on the novel Requiem (1991), written in Portuguese. This example is all the more interesting because the author refused to translate himself into Italian, leaving the translation to another native speaker. Tabucchi justifies very clearly the reasons for this choice of writing language, which was obvious to him.